JILIR journal of international law & international relations. (University of Toronto Faculty of Law and Munk Centre for International Studies, 2005)
The JILIR aims to promote critical, informed, and interdisciplinary debate on the intersection of international law and international relations. To this end, the JILIR provides a forum for contributions from Canada and abroad on matters of current concern in international affairs in general and on issues of particular interest to Canada.